Regulating zinc electroplating chemistry to achieve high energy coaxial fiber Zn ion supercapacitor for self-powered textile-based monitoring system. (March 2022) - Zhao, Jingxin; Cong, Zifeng; Hu, Jun; Lu, Hongyu; Wang, Litong; Wang, Huibo; Malyi, Oleksandr I.; Pu, Xiong; Zhang, Yanyan; Shao, Huaiyu; Tang, Yuxin; Wang, Zhong Lin
Abstract: Coaxial fiber-shaped Zn-ion hybrid supercapacitors (CFZHSCs) with high power/energy density, long cycle life, splendid mechanical stability, and high safety are promising electrochemical energy storage devices for flexible and wearable electronics. However, the poor electrochemical performance of Zn anode severely restricts their practical application. To address this challenge, a highly reversible fiber-shaped Zn anode with controlled deposition morphology is developed based on theoretical calculation guided design of highly zincophilic 3D metal-organic-frameworks derived carbon with N- and OH-containing functional groups (N, O-MOFC) scaffold, by regulating electroplating chemistry of the initial nucleation and crystal growth time of zinc metal. Benefitting from fast ion diffusion ability of the hierarchically nanostructured 3D Zn/N, O-MOFC anode on the carbon nanotube fiber (CNTF), the assembled CFZHSCs device achieves a large volumetric specific capacitance of 128.06 F cm −3 and a high volumetric energy density of 57.63 mWh cm −3, surpassing the state-of-the-art FZHSCs device. More impressively, the efficient rechargeable capability of the fiber-shaped Zn anode also enables an adequately stable CFZHSCs device with the capacitance retention of 99.20% after 10, 000 charge/discharge cycles and remarkable mechanical flexibility. As a conceptual demonstration of system integration, the as-fabricated CFZHSCs device is integrated with triboelectric nanogenerator (TENG) yarn to achieve the self-powered textile-based monitoring systems to stably detect temperature variation. Graphical Abstract: The constructed coaxial fiber-shaped Zn-ion supercapacitor realize the self-powering textile-based energy-sensor to stably monitor the temperature of the human body. ga1 Highlights: We construct a reversible fiber-shaped Zn anode by regulating the initial nucleation and crystal growth time of zinc metal. The assembled CFZHSCs device achieves a large specific capacitance 128.06 F cm −3 and a high energy density 57.63 mWh cm −3 . The CFZHSCs device embraces the excellent cyclic stability and remarkable mechanical flexibility. The CFZHSCs device is integrated with TENG yarn to achieve the self-powered textile-based monitoring systems.